2016
DOI: 10.1093/chemse/bjv080
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of a Simple Method for Determining Salt Taste Detection and Recognition Thresholds

Abstract: The aim of this study was to assess the reliability of a rapid analytical method to determine salt taste detection and recognition thresholds based on the ASTM E679 method. Reliability was evaluated according to criterion of temporal stability with a 1-week interval test-retest, with 29 participants. Thresholds were assessed by using the 3-AFC technique with 15 ascending concentrations of salt solution (1-292 mM, 1.5-fold steps) and estimated by 2 approaches: individual (geometric means) and group (graphical) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…While any explanation of this paradox is necessarily speculative, it is of note that there has been little opportunity, given the interoceptive tasks that currently exist, to equate task demands across interoceptive domains. For example, some tasks measure participants’ ability to detect interoceptive stimuli (e.g., when an obstruction is applied to respiration [ Garfinkel, Manassei, et al, 2016 ; Pollatos et al, 2016 ]); others assess the ability to determine the magnitude of interoceptive signals (such as in the muscular effort and taste tasks used in Experiments 2 and 3), whereas others measure the ability to discriminate between interoceptive signals ( Giguère et al, 2016 ). Furthermore, tasks are not generally equated for speed, accuracy, working memory, or sustained attention demands across tasks; for example, the standard heartbeat tracking task ( Schandry, 1981 ) requires a sustained period of attention for up to 100 seconds, whereas the respiratory task used by Pollatos and colleagues ( Pollatos et al, 2016 ) required participants to sustain attention for only a few seconds during a period of exhalation.…”
Section: Discussionmentioning
confidence: 99%
“…While any explanation of this paradox is necessarily speculative, it is of note that there has been little opportunity, given the interoceptive tasks that currently exist, to equate task demands across interoceptive domains. For example, some tasks measure participants’ ability to detect interoceptive stimuli (e.g., when an obstruction is applied to respiration [ Garfinkel, Manassei, et al, 2016 ; Pollatos et al, 2016 ]); others assess the ability to determine the magnitude of interoceptive signals (such as in the muscular effort and taste tasks used in Experiments 2 and 3), whereas others measure the ability to discriminate between interoceptive signals ( Giguère et al, 2016 ). Furthermore, tasks are not generally equated for speed, accuracy, working memory, or sustained attention demands across tasks; for example, the standard heartbeat tracking task ( Schandry, 1981 ) requires a sustained period of attention for up to 100 seconds, whereas the respiratory task used by Pollatos and colleagues ( Pollatos et al, 2016 ) required participants to sustain attention for only a few seconds during a period of exhalation.…”
Section: Discussionmentioning
confidence: 99%
“…By using a single 0.66 probability cut-off for all participants we were able to assess their sensitivity at the same point identified by the binomial regression model. A similar approach has been used by Giguère et al, 2016 and Jayasinghe et al, 2017 [ 67 , 68 ]. The probability of 0.66 differentiated between participants at a common intercept and is a chance-corrected detection rate.…”
Section: Methodsmentioning
confidence: 99%
“…Detection and recognition thresholds of the taste compounds were determined using the 3-AFC ascending concentration series method of limits as described in ASTM E679-04 (ASTM International, 2011). This method has been verified by Giguère et al (2016) as a fast, simple, and reliable method to assess taste thresholds. The number of subjects per age group used in this study was within the range (a minimum of 25) as suggested by Lawless (2010) for estimating taste thresholds using the forced-choice tests with ascending concentration series.…”
Section: Determination Of Sensory Thresholdsmentioning
confidence: 96%